Levobupivacaine Induces Ferroptosis by miR-489-3p/SLC7A11 Signaling in Gastric Cancer - Mao, Shun-Hong; Zhu, Chun-Hua; Nie, Yu; Yu, Jian; Wang, Lei (Frontiers in Pharmacology, 2021)
Gastric cancer is one of the most the prevalent malignancies and the therapeutic strategies for patients with gastric cancer remains limited. Local anesthetic levobupivacaine has demonstrated potential anti-cancer property, but its correlation with gastric cancer and ferroptosis is poor understood. Here, we identified the novel function of levobupivacaine in regulating ferroptosis of gastric cancer cells. The treatment of levobupivacaine suppressed gastric cancer cell viabilities and Edu-positive cell proportions. The gastric cancer cell growth was reduced by levobupivacaine in vivo. Moreover, the treatment of levobupivacaine enhanced erastin-induced inhibitory impact on gastric cancer cell viabilities. The levels of Fe2+/iron and lipid ROS were induced by levobupivacaine in erastin and RSL3-stimulated gastric cancer cells. levobupivacaine-upregulated miR-489-3p enhanced ferroptosis of gastric cancer cells by targeting SLC7A11. MiR-489-3p was involved in levobupivacaine-induced ferroptosis of gastric cancer cells. Levobupivacaine/miR-489-3p/SLC7A11 axis attenuates gastric cancer cell proliferation in vitro. Therefore, we concluded that the local anesthetic levobupivacaine induced ferroptosis of gastric cancer cells to repress gastric cancer cell growth by miR-489-3p/SLC7A11 axis.